Prediction during native and non-native language comprehension: the role of mediating factors - Ito, Aine (The University of Edinburgh, 2016)
Psycholinguistic evidence suggests that people predict upcoming words during language comprehension. While many studies have addressed what information people predict, less is known about the role of factors that potentially mediate predictive processing. This thesis examines predictions of semantic information and word form information. It investigates whether predictive processing is mediated by availability of cognitive resources and time to generate predictions, and compares predictive processing in native (L1) speakers and non-native (L2) speakers. This thesis presents two major lines of work. Two eye-tracking studies investigate prediction of semantic and word form information using a visual world paradigm. In further two ERP studies, we address the interplay of semantic and word form information in a paradigm which combines both possibilities. Experiments 1 and 2 were an eye-tracking study conducted on L1 and L2 speakers of English. The study has demonstrated that L1 and L2 speakers predict semantic information, but their predictive eye movements are delayed when they are under a cognitive load. The effects of cognitive load on predictive eye movements suggest a role of cognitive resources in language prediction in both L1 and L2 speakers. Experiments 3 and 4 were another eye-tracking study conducted on L1 and L2 speakers. The study has shown that L1 speakers predict word form information, but L2 speakers do not. Experiments 5 and 6 were an ERP study, which investigated the interplay of prediction of semantic and word form information in L1 English speakers. Consistent with the two sets of eye-tracking experiments, L1 speakers predicted both semantic and word form information, but word form was only predicted when sentences were presented at a slower rate, while semantic information was predicted at standard and slow presentation rates. Experiments 7 and 8 used the same method as Experiments 5 and 6, conducted on L2 English speakers. L2 speakers comprehended sentences incrementally, but there was no clear evidence that they predicted semantic information or word form information. Experiments 5 – 8 suggest that prediction of word form information is mediated both by nativeness of the target language and by reading rates. To conclude, both L1 and L2 speakers make predictions, but prediction of semantic information occurs only when there are enough cognitive resources available. Prediction of word form can occur in L1 speakers, but it occurs only when there is enough time available. There is no evidence that L2 speakers predict word form, suggesting a role of nativeness of the target language. The findings are consistent with the production-based prediction model of language prediction, in that prediction of word form is less likely to occur compared to prediction of semantic information. Furthermore, the findings are also consistent with the claim that not everyone makes predictions, and predictions do not always occur. The thesis concludes that prediction is additional processing for the comprehension system, and is not always implicated in the comprehension system.
Keywords: language prediction; language comprehension; sentence processing; bilingualism